2019
DOI: 10.1186/s13011-019-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher doses of naloxone are needed in the synthetic opioid era

Abstract: There has been a dramatic increase of deaths due to illicit fentanyl. We examined the pharmacology of fentanyl and reviewed data on the number of repeat doses of naloxone used to treat fentanyl overdoses. Multiple sequential doses of naloxone have been required in a certain percentage of opioid overdoses due to fentanyl. In addition, fentanyl appears to differ from other opioids as having a very rapid onset with high systemic levels found in overdose victims. A rapid competition is required by naloxone to out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 28 publications
2
118
0
Order By: Relevance
“…associated with underdosing of naloxone is an unsuccessful reversal of opioid toxicity leading to death, which outweighs the risk of opioid withdrawal [33]. This model supports the notion that higher doses of naloxone are required as a countermeasure to the new synthetic opioid epidemic [34]. Table. (TIF)…”
Section: Plos Onesupporting
confidence: 59%
“…associated with underdosing of naloxone is an unsuccessful reversal of opioid toxicity leading to death, which outweighs the risk of opioid withdrawal [33]. This model supports the notion that higher doses of naloxone are required as a countermeasure to the new synthetic opioid epidemic [34]. Table. (TIF)…”
Section: Plos Onesupporting
confidence: 59%
“…Currently, in spite of community awareness and increased access to naloxone, deaths from synthetic opioids have reached record highs and do not seem to be slowing (Baumann et al, 2018;Skolnick, 2018). This fact is coupled with increasing reports of unsuccessful resuscitation attempts with naloxone following F/FA exposure, or successful resuscitation attempts only via multiple and escalating doses (Schumann et al, 2008;Fairbairn et al, 2017;Baumann et al, 2018;Moss and Carlo, 2019). These reports are further confounded by the fact that F/FAs are being combined with multiple illicit drugs (e.g., heroin, fentanyl, carfentanil, and Xanax) of unknown quantity, quality, synthesis, and combination, and the fact that these illicit drugs are not easily assayed.…”
Section: Naloxonementioning
confidence: 99%
“…Lastly, we observed a significant correlation between percent RO and plasma NLX plasma levels and, taken together, these results support the notion that higher doses of IM NLX result in higher mu RO. Given that higher doses of naloxone could be needed to treat overdoses due to more potent synthetic opioids such as fentanyl and carfentanil [8,9], development of higher dose forms of naloxone is warranted in light of the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone (NLX) is the first line of treatment and an effective countermeasure in the event of an opioid overdose because, as a mu receptor antagonist, it is capable of rapid reversal of opioid toxicity [3]. Currently approved doses of NLX include 4 mg intranasal (IN) and 2 mg intramuscular (IM) [4] but, to date, there have been numerous reports suggesting that multiple doses of NLX may be required for successful reversal of opioid toxicity, especially when treating overdoses due to more potent synthetic opioids such as fentanyl and carfentanil that have entered the illicit drug market recently [5][6][7][8][9]. To address this issue, we previously reported that a higher dose of intramuscular naloxone (5 mg ZIMHI) has greater systemic exposure compared to the current community dose of naloxone (2 mg intramuscular and 4 mg intranasal) [10].…”
Section: Introductionmentioning
confidence: 99%